Influence of Trust Climate on Turnover Intention Mediated by Work Engagement on Workers in Indonesia - Oskar Ezra Alan Muin; Christian Haposan Pangaribuan (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study assesses the impact of trust climate on turnover intention within Indonesia’s formal employment sector, exploring the mediating function of work engagement. Employing a quantitative, explanatory research design, the study analyzed data from 315 participants, collected via an online survey, using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings indicate that trust climate enhances work engagement and conversely reduces turnover intention. Work engagement, in turn, was also found to exert a negative influence on turnover intention. This research identifies a significant indirect pathway where trust climate affects turnover intention via work engagement. This suggests that work engagement acts as a partial mediator in the relationship between the organizational trust climate and intentions to leave. Theoretically, this study enriches the human capital literature by proposing a mediation model grounded in social exchange theory. From a practical standpoint, the results offer actionable insights for organizations, emphasizing the importance of cultivating a trustworthy environment and implementing engagement initiatives to bolster employee retention.